Cartografia do Orçamento Participativo em Belo Horizonte: reflexões transescalares sobre representação política e territorial - Henrique Dias Porto (2024)
Participatory Budgeting (PB) is one of the main instruments of popular participation in urban policy ever conceived. It was created in Brazil at the end of the 1980s and has gained notoriety and prestige around the world in recent decades. One of the main Brazilian PB experiences was the case of Belo Horizonte, which began in 1993 and was active until 2016, when it was paralyzed. It is believed that the trajectory of the implementation, existence and decline of the instrument in the capital of Minas Gerais is very enlightening of the different dimensions that PB takes on as an instrument of urban policy and participatory planning, as well as the dynamics of political and territorial representation that unfolded in the city during this period. Thus, this thesis is dedicated to mapping the case of the Belo Horizonte PB, seeking to articulate, from the overlapping of different narratives, trans-scalar understandings on the themes of geopolitics, planning theory and local territorial dynamics. In this sense, from the cartographic observation of the case of the Belo Horizonte PB, reflections are made on the contemporary dynamics of political and territorial representation in urban contexts, as well as the possibilities and limitations of the PB instrument.